Eight novel ABCD1 gene mutations and three polymorphisms in patients with X-linked adrenoleukodystrophy: The first polymorphism causing an amino acid exchange - Dvoráková, L; Storkánová, G; Unterrainer, G; Hujová, J; Kmoch, S; Zeman, J; Hrebícek, M; Berger, J (Human mutation, 2001)
X-ALD is a neurological disorder associated with inherited defects in the ABCD1 (ALD) gene located on Xq28 and with impaired peroxisomal very long-chain fatty acid beta-oxidation. We examined the ABCD1 gene in probands from 11 unrelated X-ALD Czech and Slovak families by the direct sequencing of cDNA or genomic PCR products. In 10 families there were 10 different mutations, eight of which were novel. The spectrum of mutations consists of six point mutations, three microdeletions (1bp, 2bp, 4 bp), and one large deletion (229bp). In the 11th family we detected two novel single-base pair substitutions in exon 1 (c.38 A>C and c.649 A>G), both causing amino acid exchanges (N13T and K217E). Expression studies revealed that only K217E is a deleterious mutation, because a plasmid encoding ALDP with K217E was ineffective in the restoration of defective beta-oxidation in X-ALD fibroblasts. The N13T amino acid exchange, on the other hand, did not affect ALDP function. Thus, N13T represents the first polymorphism causing an amino acid exchange in the ABCD1 gene. As this polymorphism was observed neither in 100 control alleles nor in 300 X-ALD patients who have been sequenced so far world-wide, it seems to be very rare or unique. Two additional novel polymorphisms were found by the sequencing of the ABCD1 gene from our patients: c.-59 C/T in the 5'untranslated region and c.2019 C/T (F673F) in exon 10. The frequencies of these two polymorphisms, were 11/150 and 2/150 control alleles, respectively.
Keywords: ATP-Binding Cassette Transporters; dospělí; chromozom X; mastné kyseliny; 5' nepřekládaná oblast; Female; Phenotype; ABC transportér, podrodina D, člen 1; genetická vazba; dítě; Adult; Fatty Acids; ženské pohlaví; mutační analýza DNA; Amino Acid Motifs; jednonukleotidový polymorfismus; Adolescent; Slovakia; lidé; Molecular Sequence Data; ABC transportéry; Polymorphism, Single Nucleotide; DNA Mutational Analysis; membránové proteiny; Mutation, Missense; adrenoleukodystrofie; oxidace-redukce; molekulární sekvence - údaje; Palmitic Acid; missense mutace; 5' Untranslated Regions; Male; Oxidation-Reduction; Czech Republic; konzervovaná sekvence; Exons; Genetic Linkage; X Chromosome; polymorfismus genetický; alely; ATP Binding Cassette Transporter, Subfamily D, Member 1; Adrenoleukodystrophy; Česká republika; Alleles; Membrane Proteins; exony; Child; kyselina palmitová; Slovenská republika; fenotyp; mužské pohlaví; Polymorphism, Genetic; aminokyselinové motivy; mladiství; Conserved Sequence; Humans